Development of Variable Frequency Drive for Compact Three Phase Induction Motor using Discrete Components - Suparmaniam, M. V.; A. R., Yusoff; Ajisman, Apen (Universiti Malaysia Pahang, 2016)
The electric drive systems used in industrial application are enabling to increase the dynamic performance and reliability requirement. Nowadays, most of the home appliances and process industries use three-phase induction motor (TPIM) because they are simple and low cost and easy to maintain. Actually, these kinds of application do not require precise speed control using FPGA or microcontroller since there are low-performance types. This paper represents the design and development of low cost variable frequency drive (VFD) system for three-phase induction motor. Step-by-step in generating SPWM switching signal using different simple discrete components are explained thoroughly. The software used to design the SPWM and driver circuits are Multisim and Proteus. After simulation done, all the circuits are soldered appropriately and tested using oscilloscope. In addition, the study of relationship between speeds (rpm) with various frequencies is also thoroughly discussed. The type of induction motor used was three-phase squirrel cage induction motor model EM5001-3G. The speed of the motor was measured in RPM using industrial grade rotary encoder. So, overall experiment shows that this VFD made of discrete components are really can drive three-phase induction motor at low cost, easy to maintenance and do not require any specialist to repair it. Moreover, it does not require any programming or coding to build. This system also is simple because only used discrete electronic components which are widely available in market with extensive application notes which can be downloadable as free. This VFD drive system can be used for educational purposes where students can get an insight into three-phase inverter and they can design, build and testing the system by themselves.